Emplacement and exhumation history of Mesozoic granitic rocks in the Jiaonan uplift, eastern China. (15th August 2022) - Pang, Yumao; Zhao, Yinqiang; Han, Zuozhen; Zhang, Xunhua; Liu, Fengchen; Guo, Xingwei; Zhu, Xiaoqing
Graphical abstract: Highlights: Zircon U-Pb dating yielded 114 Ma and 115 Ma for Jiaonan granites. Three thermal evolution stages of the Early Cretaceous granites are revealed. The exhumation history is influenced by multiple geodynamic processes in East Asia. Abstract: The Jiaonan uplift is one part of the Sulu orogen, which is the most prominent Phanerozoic orogenic belt on the East Asian continental margin. The exhumation history of Mesozoic intrusive rocks in the Jiaonan uplift was related to intracontinental tectonics and processes since the Mesozoic time. These tectonics and processes are of great significance for the study of the regional tectonic evolution. New U–Pb zircon data of granite samples from the Jiaonan uplift yield Early Cretaceous ages (∼114 Ma and 115 Ma). Applying apatite fission-track (AFT) and zircon (U-Th)/He geochronometers to samples from the representative intrusions from the Jiaonan uplift and its adjacent area refines the exhumation and cooling history. The new age constraints and AFT thermal inverse modeling results reveal three thermal evolutionary stages after the emplacement of the Lower Cretaceous granites. Modeling results show that the Lower Cretaceous granites rapidly cooled to the AFT partial annealing zone during the Late Cretaceous, followed by a period of relatively slow cooling from the Paleocene to Eocene, and re-entered a second cooling stage since about the Oligocene. The first rapid cooling process during the Cretaceous coincided with the late rapid exhumation of the Sulu UHP metamorphic rocks, implying that they might have been dominated by a unified deep geodynamic background. The cooling event since the Oligocene might have been influenced either by Pacific subduction and/or lateral motion during the India-Asia collision.